2011
DOI: 10.1007/s12088-011-0099-0
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Meloxicam by Cunninghamella blakesleeana: Significance of Carbon and Nitrogen Source

Abstract: Influence of carbon and nitrogen source, on biotransformation of meloxicam was studied by employing Cunninghamella blakesleeana NCIM 687 with an aim to achieve maximum transformation of meloxicam and in search of new metabolites. The transformation was confirmed by HPLC and based on LC-MS-MS data and previous reports the metabolites were predicted as 5-hydroxymethyl meloxicam, 5-carboxy meloxicam and a novel metabolite. The quantification of metabolites was performed using HPLC peak areas. The results obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is the main composition of DNA, protein and acts as a building block of the cells. Recently, in the biotransformation studies of meloxicam by Cunninghamella blakesleeana , the nitrogen source was varied and it was found that ammonium nitrate was most suitable for efficient production (Prasad et al 2011 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the main composition of DNA, protein and acts as a building block of the cells. Recently, in the biotransformation studies of meloxicam by Cunninghamella blakesleeana , the nitrogen source was varied and it was found that ammonium nitrate was most suitable for efficient production (Prasad et al 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Glucose is the most preferred carbohydrate in fermentative processes and, therefore, addition of glucose at a particular concentration can help in the increased activity of the organism and thus elevated production (Prasad et al 2011 ). Also, supplementation of different carbon sources can have various effects on the morphology, biomass and production of metabolites in fungus (Jia et al 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Microbial transformation could yield novel drugs and existing drugs could be modified so as to increase activity and decrease toxicity. Sometimes, by modification of the parent drug, its side-effects could be reduced and the stability could be increased [13]. Cunninghamella blakesleeana NRRL 1369 has P450 monooxygenase.…”
Section: Conclusion and Discussionmentioning
confidence: 99%